Development of Novel SSR Markers for Flax (Linum usitatissimum L.) Using Reduced-Representation Genome Sequencing - Wu, Jianzhong; Zhao, Qian; Wu, Guangwen; Zhang, Shuquan; Jiang, Tingbo (Frontiers in Plant Science, 2017)
Flax (Linum usitatissimum L.) is a major fiber and oil yielding crop grown in northeastern China. Identification of flax molecular markers is a key step toward improving flax yield and quality via marker-assisted breeding. Simple sequence repeat (SSR) markers, which are based on genomic structural variation, are considered the most valuable type of genetic marker for this purpose. In this study, we screened 1,574 microsatellites from Linum usitatissimum L. obtained using reduced representation genome sequencing (RRGS) to systematically identify SSR markers. The resulting set of microsatellites consisted mainly of trinucleotide (56.10%) and dinucleotide (35.23%) repeats, with each motif consisting of 5 to 8 repeats. We then evaluated marker sensitivity and specificity based on samples of 48 flax isolates obtained from northeastern China. Using the new SSR panel, the results demonstrated that fiber flax and oilseed flax varieties clustered into two well separated groups. The novel SSR markers developed in this study show potential value for selection of varieties for use in flax breeding programs.